Thermokarst lake changes over the past 40 years in the Qinghai–Tibet Plateau, China - Li, Lan; Zhang, Xindi; Li, Xuan; Zhao, Shufang; Ni, Wankui; Yang, Zhenzhen (Frontiers in Environmental Science, 2022)
A thermokarst lake is generally defined as a lake that occupies a closed basin and is created by the massive melting of ground ice in ice-rich permafrost regions, which has a great impact on regional hydro-ecological equilibrium and permafrost-engineering infrastructure facilities. Global warming and increasing human activities have been accompanied by permafrost degradation and glacier retreat in the Qinghai–Tibet Plateau (QTP). The QTP, source of many international rivers in Asia, is known as the “Asian Water Tower.” The number and area of lakes in the QTP have increased in the past 40 years; however, lakes with areas of less than 1 km2 have been overlooked when calculating the water storage. To address the evolution of thermokarst lakes in the QTP, visual interpretation and the Modified Normalized Difference Water Index were applied to extract the water area based on Landsat data from the 1980s to 2020. The results indicate that thermokarst lake area was reduced from 932.5 km2 to 799.25 km2 from the 1980s to 1990. From 1990 to 2020, the number and area of lakes grew substantially, with the number increasing from 66506 to 120374 and the area increasing by 113.14% (932.5 km2 in 1980s and 1703.56 km2 in 2020). As heat carriers, thermokarst lakes transfer heat vertically and horizontally. The temperature of the surrounding permafrost rises as the number and area of lakes increase and when permafrost is extensively degraded. Longtime carbon stocks are also released into atmosphere during lake formation, which affects the regional carbon cycle.